Synthesis of Colloidal Mn2+:ZnO Quantum Dots and High-T C Ferromagnetic Nanocrystalline Thin Films - Norberg, Nick S; Kittilstved, Kevin R; Amonette, James E; Kukkadapu, Ravi K; Schwartz, Dana A; Gamelin, Daniel R (Journal of the American Chemical Society, 2004)
We report the synthesis of colloidal Mn2+-doped ZnO (Mn2+:ZnO) quantum dots and the preparation of room-temperature ferromagnetic nanocrystalline thin films. Mn2+:ZnO nanocrystals were prepared by a hydrolysis and condensation reaction in DMSO under atmospheric conditions. Synthesis was monitored by electronic absorption and electron paramagnetic resonance (EPR) spectroscopies. Zn(OAc)2 was found to strongly inhibit oxidation of Mn2+ by O2, allowing the synthesis of Mn2+:ZnO to be performed aerobically. Mn2+ ions were removed from the surfaces of as-prepared nanocrystals using dodecylamine to yield high-quality internally doped Mn2+:ZnO colloids of nearly spherical shape and uniform diameter (6.1 ± 0.7 nm). Simulations of the highly resolved X- and Q-band nanocrystal EPR spectra, combined with quantitative analysis of magnetic susceptibilities, confirmed that the manganese is substitutionally incorporated into the ZnO nanocrystals as Mn2+ with very homogeneous speciation, differing from bulk Mn2+:ZnO only in the magnitude of D-strain. Robust ferromagnetism was observed in spin-coated thin films of the nanocrystals, with 300 K saturation moments as large as 1.35 μB/Mn2+ and T C > 350 K. A distinct ferromagnetic resonance signal was observed in the EPR spectra of the ferromagnetic films. The occurrence of ferromagnetism in Mn2+:ZnO and its dependence on synthetic variables are discussed in the context of these and previous theoretical and experimental results.